Designing a strategic map and operational model of the strategies of the Iranian Judo Federation with the balanced score card method - Seyad Ehsan Amirhosseini (Islamic Azad university, Isfahan Branch, 2022)
Objective: The purpose of this research was to design a strategic map and operational model of Iran Judo Federation's strategies using the balanced scorecard method.Methodology: The research method is descriptive and practical in terms of purpose. The research data was collected in a survey and in a mixed way. The statistical population in the quantitative part was 70 people, including officials of the federation and judo boards and managers of the country's first-level judo clubs, and in the qualitative part, 12 people were judo experts. Due to the limitation of members, the statistical sample was equal to the population. The research tool was a questionnaire to determine the landscape of strategies. For data analysis, frequency percentage and chi-chi-square test were used in the quantitative part, and experts' opinions, logical induction method and strategic council meetings were used in the qualitative part.Results: The findings showed that there are four aspects of finance and development, customer, internal processes and growth and learning. 36 strategic goals, 37 criteria and 39 actions and initiatives were formulated. It can be said that with measures such as the increase of talent centers and participating clubs in basic development, the increase of talent coaches, the increase of qualitative targeted courses and the development of comparative studies and statistics, the most important international measures for the development of judo in terms of growth and learning. It will facilitate the realization of the strategies of the processes and will help the officials to achieve the foundation and considered development and professionalization of judo sport, stabilization and continuity of judo honors at the Asian and global levels.Conclusion: Due to the relationship between strategies and strategic goals, measures and actions and initiatives of the Judo Federation in different perspectives, this model has the ability to create a basis for the achievement of the country's long-term judo goals